Mean upper air flow patterns associated with spells of strong and weak northeast monsoon conditions over the Madras State in the month of November (MAUSAM, 1965)
Mean upper air flow patterns have been worked out for spells of strong and weak northeast monsoon conditions over the Madras State in the month of November and compared with the normal patterns for the month. It is noticed that the winds at 1.5 and 3. 0 km a.s.l. over the Pemnsula are mainly easterlies when the monsoon is strong, but become northerlies, when the monsoon is weak. At 6.0 and 9.0 km a.s.l. anti cyclonic cell over the Bay of Bengal is prominent during strong monsoon conditions but becomes diffuse during weak monsoon conditions, when the high pressure cell over the Arabian Sea. becomes dominant.